(untitled) - McFadden, Eleanor (Hoboken, N.J., 2007)
A valuable new edition of the trusted, practical guide to managing data in clinical trials. Regardless of size, type, or complexity, accurate results for any clinical trial are ultimately determined by the quality of the collected data. Management of Data in Clinical Trials, Second Edition explores data management and trial organization as the keys to developing an accurate and reliable clinical trial. With a focus on the traditional aspects of data collection as well as recent advances in technology, this new edition provides a complete and accessible guide to the management structure of a clinical trial, from planning and development to design and analysis. Practical approaches that result in the collection of complete and timely data are also provided.
Keywords: Clinical trials,Clinical Trials,Database management systems,Thử nghiệm lâm sàng,Thử nghiệm lâm sàng,Hệ thống quản lý dữ liệu; Data processing,Methods,Xử lý dữ liệu,Phương pháp